Quelques notes sur les articles 1, 2, 7 et 15 de la Charte canadienne des droits et libertés - Brun, Henri (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1982)
This short article simply comments on sections 1, 2, 7 and 15 of the Canadian Charter of Rights and Freedoms : That is to say, on the interpretation, freedom of expression, due process and equality clauses. The author suggests some explanations of these texts.